Association between focal amyloid deposition and cognitive impairment in individuals below the amyloid threshold - Ham, Hongki; Kim, Byeong C.; Lee, Eun Hye; Shin, Daeun; Jang, Hyemin; Kang, Sung Hoon; Yun, Jihwan; Kim, Hee Jin; Na, Duk L.; Kim, Jun Pyo; Seo, Sang Won; Cho, Soo Hyun (Frontiers in Aging Neuroscience, 2024)
Purpose: This study aimed to investigate the characteristics of individuals with amyloid levels below the threshold. To achieve this, we differentiated between two groups: those with global amyloid negativity but focal deposition (G(-)F(+)) and those without focal deposition (G(-)F(-)).Materials and Methods: A total of 2,677 participants were diagnosed with cognitive unimpairment (CU) or mild cognitive impairment (MCI). MRI-based regional centiloid (CL) values were used to establish threshold values for each brain region. After applying a cutoff of 20 rdcCL to identify amyloid positivity, participants who were globally amyloid-negative were grouped into three categories: those who showed focal amyloid uptake (G(-)F(+)), individuals without focal amyloid deposition but with relatively high CL(HC) levels comparable to those in the focal uptake group (G(-)F(-) HC)), and those with relatively low CL(LC) levels (G(-)F(-) LC). We compared the neuropsychological test results and brain structural changes between these groups using ANCOVA.The G(-)F(+) group demonstrated a lower cortical thickness (P < 0.001) than the G(-)F(-) HC group. In neuropsychological tests, the G(-)F(+) group exhibited lower the Seoul Verbal Learning Test delayed recall (SVLT-DR) and Mini Mental State Examination (MMSE), and showed progressed clinical status in the clinical dementia rating-sum of boxes (CDR-SOB) compared to the G(-)F(-) HC group (P < 0.001). The subsequent sensitivity analyses confirmed the persistence of these findings.Conclusions: Individuals with focal amyloid deposition (G(-)F(+)) exhibited higher rates of cognitive impairment compared to patients with similar levels of amyloid, underscoring the importance of monitoring the progression of focal uptake, even when it remains below the amyloid threshold.